(untitled) (Orfeu, 2025)
Harmony performance can be practiced from the time children begin playing the piano, through experimental and imitation activities (COSTA-GIOMI, 2003; 1994), which are aligned with the student’s motor development. Based on an ongoing doctoral research project, we have identified basic technical-pianistic skills so that the performance of harmonies can be accessible to children from the moment they begin playing the instrument. In this sense, the aims of this article are (1) to analyze how these technical-pianistic skills enable children to perform basic harmonies; (2) to point out pedagogical-methodological possibilities for introducing accessible, playful and motivating harmony practices for the public in question, from the earliest stages of learning the instrument. We hope to contribute to Piano Pedagogy, reducing the existing gap in the teaching of harmony in this context.